2007
DOI: 10.1080/02713680701446653
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Expression andIn VitroActivity of Antimicrobial Peptides

Abstract: Purpose-Human ocular surface epithelia express four antimicrobial peptides (APs): β-defensin (hBD) 1-3 and LL-37. Here the expression of additional APs (hBD 4-6, HE2β1; histatin-1, -3; liver expressed antimicrobial peptide-1, -2; macrophage inflammatory protein (MIP)-3α, and thymosin (T)β-4) was sought and activity against common ocular pathogens studied.Methods-AP expression was determined in human corneal and conjunctival epithelial cells (HCEC, HCjEC) by RT-PCR and in corneal sections by immunostaining. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 70 publications
2
115
1
Order By: Relevance
“…One obvious extrapolation from the current study is that the MUC5AC within tears may reduce the activities of other cationic antimicrobial peptides; however, we have previously reported that human tears do not inhibit the activity of LL-37 (31) or hBD-3 (30), which suggests that not all antimicrobial peptides are susceptible to the effects of tears in terms of their antimicrobial functions. This is also supported by evidence from a recent study showing the differential effects of tears on two rabbit ␣-defensins (36).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…One obvious extrapolation from the current study is that the MUC5AC within tears may reduce the activities of other cationic antimicrobial peptides; however, we have previously reported that human tears do not inhibit the activity of LL-37 (31) or hBD-3 (30), which suggests that not all antimicrobial peptides are susceptible to the effects of tears in terms of their antimicrobial functions. This is also supported by evidence from a recent study showing the differential effects of tears on two rabbit ␣-defensins (36).…”
Section: Discussionmentioning
confidence: 48%
“…Antimicrobial activity assays were performed to compare the activity of hBD-2 against P. aeruginosa (ATCC 27853) under our previously described conditions (30) with that in the presence of tear fluid, a more physiologically relevant condition. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since AMPs can impact the viability of P. aeruginosa (21), and because preexposure to P. aeruginosa antigens enhances AMP expression by corneal epithelia (15,35) while increasing resistance to bacterial traversal, we hypothesized that AMPs participate in epithelial defense against bacterial traversal. Small interfering RNA (siRNA) was used to knock down four different AMPs known to be expressed by human corneal epithelium (human ␤-defensins [hBD-1 to hBD3] and the cathelicidin LL-37).…”
Section: P Aeruginosa Traverses Telomerase-immortalized Multilayeredmentioning
confidence: 99%
“…[35][36][37] It has been shown to be upregulated by the cytokines IL-1b and TNF-a in cornea. 38 The exposure of hTCEpi cells to Bacillus proteins induced the increased expression and activity of MMP-9. Matrix metalloproteinase-9 is expressed during cell migration and matrix remodeling in cornea wound repair by the cornea FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%